Analysis of Financial Independence of the Jakarta Provincial Public Service Agency - Sukowasono, Dwi; Umanto, Umanto (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
The Regional Public Service Agency (BLUD) is a system implemented by the technical implementation unit of the agency/regional agency in providing services to the community who have flexibility in financial management as an exception to the provisions of regional financial management in general. The implementation of BLUD is carried out with the aim of improving public services and independence of self-financial management. The independence of BLUD financial management in this study focuses on the causes of BLUD's dependence on APBD subsidies and the problems behind it. The research method uses qualitative methods with an emphasis on document studies and interviews. The results of this study show that BLUD's financial dependence on APBD subsistence is caused by the lack of optimal BLUD financial management and administration process. For this condition, it is necessary to improve the BLUD thinking paradigm so that the performance of financial management and administration can increase so that BLUD's revenue receipts are better and the dependence on APBD subsidies can be further reduced